Rewiring tumor-associated macrophages in hepatocellular carcinoma - Han, Xue; Jin, Rui (Frontiers in Immunology, 2026)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality worldwide, with limited responsiveness to immune checkpoint inhibitors (ICIs). Accumulating evidence indicates that tumor-associated macrophages (TAMs) are central regulators of the immunosuppressive tumor microenvironment (TME) and major contributors to immune escape and therapeutic resistance in HCC. TAMs arise from both circulating monocytes and tissue-resident macrophages and exhibit remarkable plasticity, adopting diverse polarization states in response to microenvironmental cues. Beyond the classical M1/M2 paradigm, single-cell and spatial technologies have revealed a continuum of TAM phenotypes with distinct transcriptional, metabolic, and functional properties. These heterogeneous TAM subsets orchestrate angiogenesis, fibrosis, immune suppression, and resistance to immunotherapy. Consequently, TAMs have emerged as attractive therapeutic targets. Strategies aimed at limiting monocyte recruitment, reprogramming M2-like TAMs toward antitumoral phenotypes, exploiting TAMs as drug delivery vehicles, and combining TAM-targeted interventions with ICIs, radiotherapy, anti-angiogenic agents, or nanobiotechnology have shown promising preclinical and early clinical efficacy. This review summarizes current advances in understanding TAM origin, polarization heterogeneity, and functional roles in HCC, and highlights emerging TAM-centered therapeutic strategies that may improve immunotherapy outcomes and enable more precise, durable treatment responses.